GREEN WASHING WITH SPECIAL REFERENCE TO FMCG SECTOR IN PALGHAR DISTRICT. - Banerjee, Dipanwita; Sadvelkar, Deepti; Mishra, Mahendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
One of the common strategies used by unscrupulous business organizations to boost demand for their products is green washing, commonly referred to as deceptive marketing. There has been an increase in deceptive media marketing, which is bad for businesses and customers alike. Every research participant agreed that deceptive marketing tactics erode consumer trust and have a long-term detrimental impact on a company's health and sales. In this study, we attempted to determine if consumers are aware of the green washing mechanism, the impact of deceptive advertising on consumer purchasing behaviour, and the various green washing strategies used by businesses to increase sales.We used Chi square test and Cramer’s V test to prove our hypothesis through SPSS software. Our research shows green washing or misleading advertise is having significant impact on buying behavior. Consumers who are influenced by false claim without knowing the actual fact they are buying the product and thereby increasing their health risk.